NADPH oxidase NOX4 is a glycolytic regulator through mROS-HIF1α axis in thyroid carcinomas. Issue 1 (December 2018) - Tang, Ping; Dang, Hao; Huang, Jie; Xu, Tao; Yuan, Ping; Hu, Jun; Sheng, Jian-feng
Abstract The function of the NAD(P)H oxidases (NOXs) family member NOX4 is to generate reactive oxygen species (ROS), however, the molecular function of NOX4 has not been fully studied and waiting to be clarified. To elucidate the function of endogenous Nox4 in human thyroid carcinomas, papillomatosis thyroid cancer cells were used to study the cell growth by knocking down the expression of NOX4 and knocking out its functional partner p22phox/CYBA. As a result, the increasement of mitochondrial ROS(mROS) was abolished due to both knockdown of NOX4 and p22phox knockout in hypoxia, which destabilized HIF1α decreasing glycolysis and retarded cell growth. These data suggests that Nox4 is potent oncotarget due to its role in regulating glycolysis through mROS-HIF1α pathway, thereby mediating proliferation in thyroid carcinomas.